THE PRESS, WORLD WAR I AND THE «AGES AGAINST» IN THE CANARY ISLANDS, 1918-1922. - Yanes Mesa, Julio Antonio (Revista de Historia Social y de las Mentalidades, 2022)
This article analyses the exceptional weather that affected the Canary Islands, an archipelago with such a mild and benign climate, between the beginning of 1918 and at the end of 1922. Given the loss of rainfall records and the bulk of the archival documentation, we have turned to the island press, whose intensive and exhaustive use has provided us, with the opportune screening, quantitative and qualitative data of incalculable value. In addition to rescuing the evolution of meteorological time, the hemerographic sources have allowed us to recreate, by reflecting the mentalities of the time, how they were perceived and experienced, the extreme episodes by the Canarian population in the context of World War I and the postwar period.
Keywords: Methereology; World War I; Livelihood Shortage; Canary Islands